Legal Study of Interfaith Marriage According to Positive Law and Religious Law Regarding the Practice of Interfaith Marriage in Indonesia - Permana, Deni Yusup (The Easta Journal Law and Human Rights, 2024)
Interfaith marriage raises legal issues that require special attention, even though they are considered sacred in religious communities in Indonesia. The study aims to determine how Indonesia's positive laws and religion view marriage between people of different religions. Normative juridical and descriptive-analytical were used to conduct this research. After being obtained from library materials and secondary data, the data is analyzed qualitatively to obtain deductive conclusions. The study found that Law No. 1 of 1974 on Marriage stipulates marriage rules in Indonesia. It states that each spouse's religious beliefs determine whether the marriage is valid or not. Furthermore, Law Number 16 of 2019, which amends Law Number 1 of 1974, sets the age limit at which a person can marry. However couples with different religious backgrounds often face problems. Religions have different views on marriage. These concepts affect the legal status of marriage. The law affects the status and position of children, marital status, and administration of residence. Therefore, a deep understanding of positive religious and legal perspectives is necessary to resolve these legal issues in a fair and balanced manner.